Fifteen-Year Application of Manure and Chemical Fertilizers Differently Impacts Soil ARGs and Microbial Community Structure - Wang, Fenghua; Han, Wanxue; Chen, Shuaimin; Dong, Wenxu; Qiao, Min; Hu, Chunsheng; Liu, Binbin (Frontiers in Microbiology, 2020)
Manure, which contains large amounts of antibiotics and antibiotic resistance genes (ARGs), is widely used in agricultural soil and may lead to the evolution and dispersal of ARGs in the soil environment. In the present study, soils receiving 15-year manure or chemical fertilizers were sampled in the North China Plain (NCP), one of the most intensive agricultural areas in China. High-throughput quantitative PCR and sequencing technologies were employed to assess the effect of long-term manure or chemical fertilizer application on the distribution of ARGs and microbial communities. A total of 114 unique ARGs, were successfully amplified from all soil samples. Manure application markedly increased the relative abundance and detectable numbers of ARGs, with up to 0.23 copies/16S rRNA gene and 81 unique ARGs. The increased abundance of ARGs in manure-fertilized soil mainly caused by boosting the abundance of soil indigenous ARGs. In contrast, chemical fertilizers only moderately affected the diversity of ARGs and had no significant effect on the relative abundance of total ARGs. In addition, manure application boosted the abundance of the mobile genetic elements (MGEs), which were significantly and positively correlated with most types of ARGs, indicating that horizontal gene transfer via MGEs may play an important role in the spread of ARGs. Furthermore, application of manure and chemical fertilizers significantly affected microbial community structure and variation partitioning analysis showed that microbial community shifts represented the major driver shaping the antibiotic resistome. Taken together, our results provide insight into the long-term effects of manure and chemical fertilization on the dissemination of ARGs in intensive agricultural ecosystems.